Correlation between posterior teeth loss and temporomandibular joint disorder symptoms in adult patients [version 1; peer review: 2 approved] - Batool Hussein Ayaz; May Wathiq Al-Khudhairy (F1000Research)
Background/Objectives The relation between TMD and posterior tooth loss is still up for debate and is a topic of constant discussion. The present study aimed to find a correlation between posterior teeth loss and TMJ disorder symptoms in adult patients. Methods A total of fifty patients were selected for the study. First, intra-oral dental examination recorded all missing posterior teeth, the teeth numbers, type of missing teeth (except third molars). All existing teeth are examined during the clinical examination to identify any odontogenic causes for pain if present. Second, patients were asked to fill in the Arabic-translated form of the DC/TMD Axis I symptom questionnaire. Third, the DC/TMD Axis II protocol was applied to each patient and the examination form was completed by the examiner during the clinical examination. Results Disc displacement with reduction is more likely to cause headache, pain, and clicking. A statistically significant positive correlation was found between age and the number of missing teeth. Furthermore, a statistically significant negative correlation was found between age and maximum unassisted mouth opening, and the number of missing teeth and maximum unassisted mouth opening. Logistics regression analysis showed clicking was significantly associated and 13.8 (OR) times more likely to have TMD. Conclusions The current study reported that patients with TMD are more likely to have pain, headache, clicking, and a decrease in maximum mouth opening. There was a correlation between clicking and TMJ disorder, and the number of tooth loss and TMJ disorder.